Math, asked by jitengorai5510, 1 year ago

please solve it with steps by step​

Attachments:

Answers

Answered by Anonymous
0
alpha + beta = -b/a

1/3 + beta = 10/3

beta = 10/3 - 1/3

beta = 9/3

beta = 3

Another zero is 3

alpha × beta = c/a

1/3×3 = c/3

3/3 = c/3 (on comparing)

c = 3 and hence p = 3.


Answer:- Option B
Answered by Anonymous
3

HEYA \:  \\  \\ in \: a \: general \: quadratic \: Equation \: say \\ ax {}^{2}  + bx + c = 0 \: we \: have \\  \\  \alpha  +  \beta  =  - b \div a \\ and \\  \alpha  \beta  = c \div a \\  \\ here \:  in \:  \: 3x {}^{2}   -  10 + p \\  \\  \alpha  +  \beta  = 10 \div 3 \\  and \\  \alpha  \beta  = p \div 3 \\  \\  \alpha  = 1 \div 3 \:  \:  \: (given \: ) \\  \\ (1 \div 3) +  \beta  = 10 \div 3 \\  \\  \beta  = 3 \\   \\ (1 \div 3) \times (3) = p \div 3 \\  \\ p = 3 \\  \\ so \:  \: the \: value \: of \: p \: is \: 3 \: and \: the \: other \: root \: is \: 3

Similar questions